Toward a Decolonial Praxis in History of Education Research: An Exploration of The Conversations as a Collective Study Practice - Van Ruyskensvelde, Sarah; Berghmans, Mieke (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This paper explores the potential for a decolonial praxis in history of education research. It argues that history of education scholarship, despite its inclusion of critical post- and decolonial perspectives, remains largely entrenched in a modernist logics of scholarly knowledge production. This paper proposes an alternative approach by examining ‘The Conversations’, as an example of a locally-embedded practice of collective study that we undertook in the Spring of 2022 in Belgium. Inspired by decolonial scholarship and decoloniality research, we argue that such an alternative approach to historical study and research may help in connecting the discipline’s commitment to a critical study of the (colonial and imperial) past with the activation of possible futures, and promote alternative ecologies of knowledge.